Increased Serum Level of Interleukin-10 Predicts Poor Survival and Early Recurrence in Patients With Peripheral T-Cell Lymphomas - Zhang, Yan; Zheng, Yanlong; Shou, Lihong; Shi, Yuanfei; Shen, Huafei; Zhu, Mingyu; Ye, Xiujin; Jin, Jie; Xie, Wanzhuo (Frontiers in Oncology, 2020)
Peripheral T-cell lymphoma (PTCL) is a heterogeneous group of lymphoproliferative disorder arising from mature T-cells. It has multiple subtypes and most of them have poor prognosis. Interleukin-10 (IL-10) is an anti-inflammatory cytokine with important immunoregulatory functions. It had been shown to play a key role in pro-tumor effects in vivo. Therefore, we conducted a retrospective study of 205 adult PTCL patients and assessed the prognostic role of serum level of IL-10 in the complete response (CR), overall survival (OS) and early recurrence. We found patients with IL-10≥3.6pg/ml achieved a lower CR rate and higher 1-year recurrence rate than patients with IL-10＜3.6pg/ml (14.4% vs. 51.9%; 17.6% vs. 49.5%). On multivariate analysis, high IL-10 levels were independent and significant unfavorable prognostic factors with worse OS and higher early recurrence among the PTCL patients. Thus, measurement of serum IL-10 levels are useful for predicting the prognosis and for determining a suitable treatment strategy for PTCL patients. In the near future, IL-10 might be a valuable target for immune therapy as an alternative treatment strategy for patients with PTCL.